Corticosteroids combined with infliximab vs. corticosteroids sequential infliximab for acute severe ulcerative colitis with mucosal deficiency: a retrospective study - Xiaolei Liu; Xianmin Xue; Xiaojing Zhu; Jun Liu; Yongquan Shi; Min Chen (Frontiers in Medicine)
IntroductionMucosal deficiency is one of the most challenging conditions in patients with acute severe ulcerative colitis (ASUC). Intravenous corticosteroids (CS) are the first-line treatment, with infliximab (IFX) used as a rescue therapy. However, the efficacy remains unsatisfactory. We investigated whether CS combined with IFX as first-line therapy would improve outcomes in patients with ASUC with mucosal deficiency.MethodsA retrospective study was performed at a tertiary inflammatory bowel disease center. The primary outcomes included clinical remission, endoscopic improvement, and endoscopic remission at week 14. The secondary outcomes included the colectomy rate within 90 days and durable clinical remission.ResultsA total of 43 patients with ASUC with mucosal deficiency were included in the analysis (25 in the CS combined with the IFX group and 18 in the CS sequential IFX group). At week 14, endoscopic improvement was observed in 21 of 25 patients (84.0%) receiving the CS combined with the IFX regimen, compared to 9 of 18 (50.0%) patients receiving the CS sequential IFX regimen (p = 0.017). Durable clinical remission rates were significantly higher in the combined group than in the sequential group (85.7% vs. 35.7%, p = 0.004). There was no statistically significant difference between the two groups in terms of clinical and endoscopic remission at week 14 or colectomy rate within 90 days. Multivariate analysis confirmed that the CS combined with the IFX regimen was an independent predictive factor for a higher endoscopic improvement rate at week 14 (odds ratio (OR) 8.428, 95%confidence interval (CI) 1.539–46.153, p = 0.014) and a higher durable clinical remission rate (OR 10.800, 95%CI 2.095–55.666, p = 0.004).ConclusionCS combined with IFX as first-line therapy may be an effective induction strategy in patients with ASUC with mucosal deficiency. Further large-scale, multicenter prospective studies are needed.